Challenges Faced by English Education Students in Mastering Vocabulary Through Online Learning Systems - Sadewi, Ni Ketut Asta Denny; Mahardika, I Gusti Ngurah Agung Wijaya; Mahendra, Made Wahyu (Journal of English Education Program, 2024)
Vocabulary is the primary skill EFL students need to speak English fluently. It is not as simple as one may think of learning English vocabulary by simply recalling words"™ meanings and pronunciations; there are many other factors to consider as well, such as their usage and connotation. Therefore, this research aims to discover the difficulties English education students face in mastering English vocabulary during the online learning system and the factors underlying these difficulties. A descriptive design was used.   Questionnaires, observations, and interviews were used as data collection techniques. The data analysis techniques used were Likert-scale analysis for quantitative data and condensation, data display, and conclusion drawing/verification. The results showed that students had linguistic difficulties, such as range, connotation, idiomaticity, length and complexity, pronunciation, grammar, and meaning. Based on these difficulties, there were linguistic and non-linguistic factors that underlie the challenges faced by students